Human parasitology - Bogitsh, Burton J. (Burton Jerome) (Academic Press, 2012)
Human Parasitology emphasizes a medical perspective while incorporating functional morphology, physiology, biochemistry, and immunology to enhance appreciation of the diverse implications of parasitism. Bridging the gap between classical clinical parasitology texts and traditional encyclopedic treatises, Human Parasitology appeals to students interested in the medical aspects of parasitology and those who require a solid foundation in the biology of parasites. This fourth edition has been fully revised to integrate the most recent molecular discoveries about mosquitoes, ticks and other arthropods as vectors, as well as the most effective therapeutic regimens. New to this Edition: . Features expanded coverage of the evolution of parasitism and an extensive update to immunology of parasite-host interactions . Offers an enhanced art program featuring life cycle illustrations and additional SEM and TEM micrographs . New "Host Immune Response" section for each organism Presents various parasites and examines how they interact with their hosts and respond to new treatmentsEasy to read with photographs, diagrams, and clinical case pictures throughout.